2005
DOI: 10.1080/15216540500090793
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide-induced Cell Death in Arabidopsis: Transcriptional and Mutant Analysis Reveals a Role of an Oxoglutarate-dependent Dioxygenase Gene in the Cell Death Process

Abstract: SummaryHydrogen peroxide is a major regulator of plant programmed cell death (PCD) but little is known about the downstream genes from the H 2 O 2 -signaling network that mediate the cell death. To address this question, a novel system for studying H 2 O 2 -induced programmed cell death in Arabidopsis thaliana was used. The catalase inhibitor aminotriazole (AT) reduced the catalase activity and caused endogenous accumulation of hydrogen peroxide that eventually triggered cell death. Microarray analysis with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 33 publications
1
70
0
Order By: Relevance
“…A similar effect was observed by treating the roGFP2-seedlings with the catalase inhibitor 3-amino-1,2,4-triazole (3-AT; Fig. 1C; Gechev et al, 2005) or with exogenous H 2 O 2 (data not shown). In spite of the clear effect, it is difficult to assess whether the oxidation of the roGFP2 probe upon treatments with cadmium, 3-AT, or H 2 O 2 might be mediated by a partial oxidation of the glutathione pool or alternatively achieved by other means (e.g.…”
Section: Cadmium Induces Accumulation Of No and Cytosolic Oxidation Imentioning
confidence: 49%
“…A similar effect was observed by treating the roGFP2-seedlings with the catalase inhibitor 3-amino-1,2,4-triazole (3-AT; Fig. 1C; Gechev et al, 2005) or with exogenous H 2 O 2 (data not shown). In spite of the clear effect, it is difficult to assess whether the oxidation of the roGFP2 probe upon treatments with cadmium, 3-AT, or H 2 O 2 might be mediated by a partial oxidation of the glutathione pool or alternatively achieved by other means (e.g.…”
Section: Cadmium Induces Accumulation Of No and Cytosolic Oxidation Imentioning
confidence: 49%
“…WRKY75, together with the NPR1-dependent WRKY 46, are the only WRKYs detected here as early SAIGs, that have not been previously associated to pathogen-induced defense responses (Eulgem and Somssich 2007). WRKY75 has been reported to be involved in H 2 O 2 -induced cell death and as a modulator of phosphate acquisition and root development (Gechev et al 2005;Devaiah et al 2007). The function of ANAC102 and WRKY75 in the defense reaction in Arabidopsis remains to be characterized.…”
Section: Discussionmentioning
confidence: 96%
“…There are also negative correlations to both antisense and insertional mutants of AOX1 linked to the production of O 2 .2 and H 2 O 2 , again in mitochondria (Umbach et al, 2005;Giraud et al, 2008), suggesting that mitochondria may play a role in ROS signaling during senescence in both tissues. Peroxisomal ROS also may act as a signal in petal senescence, as a good correlation was obtained to amidotriazole treatment (Gechev et al, 2005), thought to induce the production of H 2 O 2 in peroxisomes. Out of the 44 ROS-induced transcription factors analyzed by Rosenwasser et al (2011), approximately half (23) were up-regulated in one or more stages of dark-induced senescence in leaves.…”
Section: Ros Generation and Scavenging: Spatiotemporal Effectsmentioning
confidence: 98%